2023
DOI: 10.3390/nano13030550
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties in a ZnS/CdS/ZnS Core/Shell/Shell Spherical Quantum Dot: Electric and Magnetic Field and Donor Impurity Effects

Abstract: A theoretical analysis of optical properties in a ZnS/CdS/ZnS core/shell/shell spherical quantum dot was carried out within the effective mass approximation. The corresponding Schrödinger equation was solved using the finite element method via the 2D axis-symmetric module of COMSOL-Multiphysics software. Calculations included variations of internal dot radius, the application of electric and magnetic fields (both oriented along z-direction), as well as the presence of on-center donor impurity. Reported optical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Additionally, by applying various model potentials inside of the Hamiltonian we can investigate different material compositions and band structures such as core/shell, core/shell/shell, type II band alignment 30-35, etc. Moreover, this method simplifies the consideration of the external electrical, magnetic, and laser fields by modifying the terms inside of the Hamiltonian [36][37][38][39][40] . Intraband optical properties have garnered significant interest due to their implications for novel optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, by applying various model potentials inside of the Hamiltonian we can investigate different material compositions and band structures such as core/shell, core/shell/shell, type II band alignment 30-35, etc. Moreover, this method simplifies the consideration of the external electrical, magnetic, and laser fields by modifying the terms inside of the Hamiltonian [36][37][38][39][40] . Intraband optical properties have garnered significant interest due to their implications for novel optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Within this experimental suggestion, this article focused on the square well potential. Coating the quantum dot core with different bandgap semiconductor material creates a unique category known as core-shell quantum dots (CSQDs) [24][25][26][27][28]. Core/shell quantum dot systems (CSQDs) are one of the greatest models for new fields in nanotechnology applications thanks to their exceptional physical proprieties such as three-dimensional quantum confinement of charge carriers and discretization of the energy spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, since it changes the effective potential profile of the external electric field applied to the structure, it can be used as a tuning parameter on the electronic and optical properties of the structure. For this reason, many theoretical and experimental studies have been carried out on quantum dots under electric field or containing impurities [57][58][59][60][61]. The optical properties of the CdS/ZnS core/shell spherical quantum dot for the central donor impurity under the electric and magnetic field were calculated by K Hasanirokh et al It was observed that the transition energy decreased as the core radius and external magnetic field increased, thus the resonance peaks were redshifted.…”
Section: Introductionmentioning
confidence: 99%
“…These systems are highly sensitive to geometry, size, and external probes, such as magnetic and electric fields [1][2][3][4]. They are also influenced by the shallow-donor and -acceptor impurities [5][6][7], neutral and charged excitons [8][9][10], intense resonant and non-resonant lasers [11], hydrostatic pressure, temperature [12], and the inclusion of spin-orbit and Zeeman effects, represented by the Rashba and Dresselhaus terms [13,14]. All these effects significantly modify the electronic, optical, thermal, and mechanical properties of semiconductor nanostructures.…”
Section: Introductionmentioning
confidence: 99%